Kesesuaian Kurikulum Program Studi Pendidikan Teknik Bangunan Universitas Negeri Jakarta Dilihat dari Kompetensi Kerja Berdasarkan Standar Kompetensi Kerja Nasional Indonesia (SKKNI) Sektor Jasa Konstruksi - Dyone Septianis; R Eka; Gina (Jurnal Pensil : Pendidikan Teknik Sipil, 2013)
The Objectives of this study to determine the suitability of the curriculum percentage Building Technical Education Program Studies, State University of Jakarta seen from the competence requirements of construction work in the world of work. Where the research conducted in the Department of Civil Engineering, State University of Jakarta. The method used is the method of observation. The data used in this study is SKKNI of position Young Experts Implementing Structure, Young Experts Construction Management, Skilled Construction Supervisors, and young Experts Quantity Surveyor. Data used for the course syllabus related to the job, the Construction Management, Science of Building Materials, Health and Safety, Practice of Soil Mechanics, Budget Plan, Environmental Impact Assessment, and Practice Test Materials. Data processing is done by creating a checklist tables and calculation of the percentage. Results of this study are subject Construction Management 50% according, Science of Buiding Materials 92,85% according, Health and Safety 28,57% according, Practice of Soil Mechanics 92,85% according, Budget Plan 85,71% according, Environmental Impact Assessment 14,28% according, and Practice Test Materials 85,71% according. There is congruence between the Education Program Building Engineering curriculum, State University of Jakarta with SKKNI. Of 7 subjects who reviewed syllabus, 4 course syllabus is in accordance with SKKNI, 2 course syllabus is quite in accordance with SKKNI, and 1 course syllabus is not in accordance with SKKNI